The influence of surface hardness on the fretting wear of steel pairs: its role in debris retention in the contact - Lemm, J.D.; Warmuth, A.R.; Pearson, S.R.; Shipway, P.H. (Elsevier, 2014)
The influence of specimen hardness (between 275 kgf mm−2 and 835 kgf mm−2) in an AISI Type O1 steel-on-steel fretting contact was examined. In equal-hardness pairs, a variation in the wear volume of around 20% across the range of hardnesses examined was observed. However, in pairs where the two specimens in the couple had different hardnesses, a critical hardness differential threshold existed, above which the wear was predominantly associated with the harder specimen (with debris embedment on the softer specimen surface). This retention of debris provides protection of that surface from further wear and also results in accelerated wear of the harder counterface due to abrasion by the oxide debris bed which has built up on the opposing specimen.